Brokers’ Stock Ratings Distributions and the Returns from their Stock Recommendations: Evidence Post-NASD Rule2 711 - CHEN, Chih-Ying (Institutional Knowledge at Singapore Management University, 2013)
NASD 2711 requires brokers to disclose their overall ratings distribution and the percentage of their investment banking customers within each rating. Based on research reports of 50 large brokers between 2003 and 2011, we find an upward trend in the overall buy percentage (BUY percentage) and a decrease in the percentage of investment banking customers in the buy recommendations (IB percentage). Furthermore, the profitability of upgrade to buy (initiation as buy) recommendations is negatively (positively) associated with the disclosed IB (BUY) percentage, and IB (BUY) percentage is negatively (positively) associated with earnings forecast accuracy. Together, the evidence is consistent with a relatively high BUY percentage largely stemming from brokers’ selective coverage of better firms and the IB percentage mainly capturing the degree of optimistic bias in analysts’ recommendations. We also find evidence that investors do not fully understand the implications of these percentages.